HBR's 10 must reads on leadership - Harvard Business School (Boston, Mass. : Harvard Business Review Press, 2011)
HBR's 10 Must Reads On Leadership will inspire you to:Motivate others to excel. Build your team's self-confidence in others. Provoke positive change. Set direction. Encourage smart risk-taking. Manage with tough empathy. Credit others for your success. Increase self-awareness. Draw strength from adversity. This collection of best-selling articles includes: featured article "What Makes an Effective Executive" by Peter F. Drucker, "What Makes a Leader?" "What Leaders Really Do," "The Work of Leadership," "Why Should Anyone Be Led by You?" "Crucibles of Leadership," "Level 5 Leadership: The Triumph of Humility and Fierce Resolve," "Seven Transformations of Leadership," "Discovering Your Authentic Leadership," and "In Praise of the Incomplete Leader."
Includes index.
Tặng
Keywords: Leadership